2014
DOI: 10.3892/ijo.2014.2568
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 3 promotes pancreatic cancer cell proliferation, invasion and increases drug-resistance through histone modification of P27, P53 and Bax

Abstract: Abstract. Pancreatic cancer is one of the most aggressive solid malignancies with a dismal survival rate. Recent studies have shown that high expression levels of histone deacetylase 3 (HDAC3) correlate with malignant phenotype. However, the expression patterns and biological role of HDAC3 in pancreatic cancer remain unclear. In this study, our data showed that a higher level of HDAC3 protein expression was found in pancreatic cancer as compared to paired paracancerous tissues. Consistently, higher expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Inhibition of HDAC3 activity by MI192 was subsequently assessed by evaluating specific acetylation of histone H3, the downstream target of HDAC3. 21 We found that MI192 increased specific histone H3 acetylation, and HDAC3 overexpression reversed this effect (Figures 4a, b and d). …”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Inhibition of HDAC3 activity by MI192 was subsequently assessed by evaluating specific acetylation of histone H3, the downstream target of HDAC3. 21 We found that MI192 increased specific histone H3 acetylation, and HDAC3 overexpression reversed this effect (Figures 4a, b and d). …”
Section: Resultsmentioning
confidence: 67%
“…We investigated the effects of HDAC3 on their downstream targets following MI192 treatment, including acetylated α -histone3, P53 and Bax. 21 MI192-induced caspase substrate (polyADP ribose polymerase (PARP) and caspase-3) cleavage and P53 expression were mimicked by HDAC3 knockdown (Figures 3d and e). Altogether, these results indicate that HDAC3 participated in MI192-induced apoptosis in CCA cells and that HDAC3 might be the target of MI192.…”
Section: Resultsmentioning
confidence: 99%
“…The related TBLR1 acts as a co-activator to repress prostate cancer proliferation via the androgen receptor (AR) [90]. Jiao et al reported that HDAC3 was upregulated in human pancreatic cancer and depletion of HDAC3 decreased the cell proliferation in vitro [91].…”
Section: The Gps2 Subunit Of the Hdac3 Co-repressor Complexmentioning
confidence: 99%
“…Overexpression of HDAC3 has been reported in numerous cancer types, such as lung, colorectal, and gastric cancer, as well as in prostate cancer. Currently, there is increasing interest in HDAC3 as a promising therapeutic target in multiple myeloma, leukemia, and gastric cancer …”
Section: Expression Of Hdacs In Cancersmentioning
confidence: 99%